Pan-Americanism in dispute. U.S. leaders, Bolívar, and San Martín in the centenaries of the Monroe Doctrine and the Amphictyonic Congress of Panama (1923-1926) - Amorebieta y Vera, María Laura (2024)
This paper analyzes the representations of U.S. statesmen, Bolívar, and San Martín during the centenaries of the Monroe Doctrine (1923) and the Congress of Panama (1926). On the one hand, it examines the characterizations of U.S. leaders and Bolívar, as well as the connections established between them, in the public interventions of various agents and articulators of U.S. Pan-American policy in the Americas during both commemorations. On the other hand, it explores the tensions and exchanges that these operations generated with "Bolivarian" political and literary referents, who insisted on presenting the Liberator as the unique father of Pan-Americanism. Finally, this article focuses on the efforts of some important politicians and intellectuals of Argentine and Chilean origin who tried to attribute to San Martín and other historical figures of the time a significant role in the birth of continental solidarity and cooperation. Ultimately, I argue that these centenaries triggered a series of complex political-ideological interactions among numerous diplomats, politicians, and intellectuals from across the continent, proving that the 1920s was a time of strong hegemonic expectations in which history became a powerful and effective resource in the attempt to reorganize and/or secure the hierarchies of the inter-American order.